Triplet Exciton Sensitization of Silicon Mediated by Defect States in Hafnium Oxynitride - Nagaya, Narumi (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2024 The Author(s). Advanced Materials published by Wiley‐VCH GmbH.